Impact of Climate Change on Sugarcane Farmers Income and Key Factor of Adaptation Dan Faktor Penentu Adaptasi - Arum Sekar Buana; Angraeni Hadi Pratiwi; Aditia Fradito (Gontor AGROTECH Science Journal, 2020)
Agriculture is a key area of economic development of Indonesia because around 44% of the Indonesian population is employed in agriculture. Climate change causes a decrease in agricultural production so that the impact on agricultural commodity price increases. The influence of climate change on crop production varies greatly among regions. The aim of this study to analyze the influence of climatic elements, sugarcane farm income and farmers' adaptation to climate change in the Palaan village. The data analysis was conducted by classifying data obtained from sampling into quantitative and qualitative. The results showed  26% sugarcane farmers have heard and felt the phenomenon of climate change, but they don’t understand the concept of climate change, while 74%  farmers have never heard of climate change. The analysis usahatani cane in the Palaan village has very low of economic benefits. The farmers have to adapt the form of improved planting land management, reduction of arable land and farmers switched professions to become entrepreneur. A significant factor influence farmers in adapting to climate change is the understanding of farmers on climate change.